The low global burden of trichinellosis: evidence and implications. Issue 2 (February 2015) - Devleesschauwer, Brecht; Praet, Nicolas; Speybroeck, Niko; Torgerson, Paul R.; Haagsma, Juanita A.; De Smet, Kris; Murrell, K. Darwin; Pozio, Edoardo; Dorny, Pierre
Abstract : Graphical abstract: Highlights: Globally, human trichinellosis is responsible for a mean estimated 76 healthy life years lost per billion people per year. This global burden is much lower than that of other foodborne parasitic diseases. The World Health Organization European region is responsible for 69% of the global burden. These findings support the revision of current Trichinella meat inspection measures towards more cost-effective programs. Abstract: Trichinellosis is a cosmopolitan foodborne disease that may result in severe health disorders and even death. Despite international awareness of the public health risk associated with trichinellosis, current data on its public health impact are still lacking. Therefore we assessed, for the first known time, the global burden of trichinellosis using the Disability-Adjusted Life Year metric. The global number of Disability-Adjusted Life Years due to trichinellosis was estimated to be 76 per billion persons per year (95% credible interval: 38–129). The World Health Organization European Region was the main contributor to this global burden, followed by the WHO region of the Americas and the World Health Organization Western Pacific region. The global burden of trichinellosis is much lower than that of other foodborne parasitic diseases and is in sharp contrast to the high budget allocated to prevent the disease in many industrialised countries. To decrease the uncertainty around the current estimates, more knowledge is needed on the level of underreporting of clinical trichinellosis in different parts of the world.